Caries Etiology and Preventive Measures - Meyer, Frederic; Schulze zur Wiesche, Erik; Amaechi, Bennett T.; Limeback, Hardy; Enax, Joachim (European Journal of Dentistry, 2024)
Caries is a widespread disease in both children and adults. Caries is caused by the conversion of fermentable carbohydrates by plaque bacteria into acids on the tooth surface. Thus, it is important to focus on sugar reduction and plaque control. For efficient plaque removal/control, state-of-the-art toothpastes contain various active ingredients such as antimicrobial agents (e.g., chlorhexidine, stannous salts, and zinc salts), abrasives (e.g., calcium carbonate, calcium phosphates, and hydrated silica), surfactants (e.g., sodium lauryl sulfate and sodium methyl cocoyl taurate), and natural compounds (e.g., polyphenols and xylitol). Agents with pH-buffering and calcium-releasing properties (e.g., calcium carbonate and calcium phosphates) and biomimetic actives (e.g., hydroxyapatite) reverse the effects of the acids. Additionally, modern toothbrushes (i.e., electric toothbrushes) as well as dental floss and interdental brushes significantly help remove plaque from dental surfaces including interproximal surfaces. In conclusion, modern concepts in caries prevention should focus not only on tooth remineralization alone but also on the control of all the key factors involved in caries development.
Keywords: caries; teeth; plaque; toothpaste; fluoride; hydroxyapatite; prevention; oral care